Om kirkesagn og ødekirker: Muntlig tradisjon og stedsnavn som kilder for kirkeforskningen - Brendalsmo, Jan; Stylegar, Frans-Arne (Hikuin, 2003)
Of Migratory Legends and Deserted Churches By Jan Brendalsmo & Frans-Arne Stylegar The main purpose of the article is to argue for observance of oral tradition as a source to deserted medieval churches. Such churches are referred to in place-names, where church- (kirke, kapell) or priest- (prest) are part of the name (eg. Kirkeby, Presterud, Kirkeåketeigen, Kapelløya). Often there are folk tales connected to these places. Some tales just tell that there once stood a church on a specific site, the site often having one of the above mentioned type of name. In other cases there is no name to support the folk tale. Then there are the so-called migratory legends, which tell that the local farmers started to build a church on a specific place, but what was built during daytime was removed to another place at night by supra-natural powers. And there the church was eventually built. A few examples are presented, from the county of Vest-Agder in the south of Norway, where the authors have excavated some of these legendary churches. The various types of tradition in Vest-Agder are then discussed and grouped, with emphasis put on three geographical areas where tradition is especially plentiful. Finally, it is argued that by treating folk tradition as any other source for scientific research, it is possible to develop a much broader understanding of the erection of religious buildings in the medieval periode. A theoretical reason is given for an approach of this kind, and an attempt at decoding the migratory legends is presented.